Effectiveness of Washing Procedures in Reducing Salmonella enterica and Listeria monocytogenes on a Raw Leafy Green Vegetable (Eruca vesicaria) - Pezzuto, Alessandra; Belluco, Simone; Losasso, Carmen; Patuzzi, Ilaria; Bordin, Paola; Piovesana, Alessia; Comin, Damiano; Mioni, Renzo; Ricci, Antonia (Frontiers in Microbiology, 2016)
Vegetables are an important source of nutrients, but they can host a large microbial population, particularly bacteria. Vegetables are an important source of nutrients, but they can host a large microbial population, particularly bacteria. Foodborne pathogens can contaminate raw vegetables at any stage of their production process with a potential for human infection. Appropriate washing can mitigate the risk of foodborne illness consequent to vegetable consumption by reducing pathogen levels, but few data are available to assess the efficacy of different practices. In the present work, six different washing methods, in the presence or absence of sanitisers (peracetic acid and percitric acid, sodium bicarbonate, sodium hypochlorite) and vinegar, were tested for their effectiveness in reducing Salmonella and Listeria counts after artificial contamination of raw rocket (Eruca vescicaria). Results showed that washing with sodium hypochlorite (200 mg/L) was the only method able to produce a significant 2 Log reduction of Salmonella counts, but only in the case of high initial contamination (7 Log CFU/g), suggesting potential harmful effects for consumers could occur. In the case of Listeria monocytogenes, all the examined washing methods were effective, with 200 mg/L sodium hypochlorite solution and a solution of peracetic and percitric acids displaying the best performances (2 and 1.5 Log reductions, respectively). This highlights the importance of targeting consumers on fit for purpose and safe washing practices to circumvent vegetable contamination by foodborne pathogens.